2018
DOI: 10.1039/c8cc02386g
|View full text |Cite
|
Sign up to set email alerts
|

Enabling multi-electron reaction of ε-VOPO4 to reach theoretical capacity for lithium-ion batteries

Abstract: By controlling the morphology and particle size of the epsilon polymorph of vanadyl phosphate, ε-VOPO4, it can fully reversibly intercalate two Li-ions and reach the theoretical capacity of 305 mA h g-1 over two voltage plateaus at about 4.0 and 2.5 V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 19 publications
6
59
0
Order By: Relevance
“…[ 12 ] We will show later, that even in the optimized nanocrystalline ε‐VOPO 4 /graphene material, the rate performance is limited by the slower high‐voltage process, which remains one of the major limitations of this material. [ 13 ]…”
Section: Lixvopo4 (X = 0 1) Polymorphism and Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 ] We will show later, that even in the optimized nanocrystalline ε‐VOPO 4 /graphene material, the rate performance is limited by the slower high‐voltage process, which remains one of the major limitations of this material. [ 13 ]…”
Section: Lixvopo4 (X = 0 1) Polymorphism and Stabilitymentioning
confidence: 99%
“…[ 21 ] Further insights into the Li 2 VOPO 4 structure were obtained using nanocrystalline ε‐VOPO 4 as a starting material. [ 13,22 ] In the paper by Siu et al. [ 13 ] we have shown that two Li can be intercalated into ε‐VOPO 4 by comparison of 7 Li NMR spectra obtained by chemical and electrochemical lithiation.…”
Section: Metastable Structures Of Lixvopo4 (X = 15 175 2) Phases:mentioning
confidence: 99%
See 1 more Smart Citation
“…ε-VOPO4 investigated in the present study was prepared by hydrothermal synthesis. 43 Thin laminates for XAS investigation were prepared by mixing ε-VOPO4 powder with graphene and polyvinylidene fluorine (PVDF) as binder in a weight ratio 75:15:10 using 1-methyl-2pyrrolidinine (NMP) as the solvent. The resultant slurry was tape cast onto an aluminum foil and dried in air at 60 °C.…”
Section: Iib Sample Preparation Detailsmentioning
confidence: 99%
“…The ε‐VOPO 4 system is considered to be one of the most promising electrodes to provide 2‐e reactions. The theoretical 2‐e capacity has been achieved by controlling the morphology and particle size of ε‐VOPO 4 until the most recent . In addition, three forms of VOPO 4 can add one Na + ion to form three NaVOPO 4 polymorphisms .…”
Section: Vanadium‐based Polyanionic Compoundsmentioning
confidence: 99%